Using speculative methods to challenge the invisibility and inevitability of data in education - Noteboom, Joe; Ross, Jen (Proceedings of the International Conference on Networked Learning, 2024)
Speculation is a resource for critical analysis of data-driven postdigital education. In particular, speculative methods help researchers challenge the invisibility of data-driven educational practices, and thereby unsettle the apparent inevitability of data futures. Working against these tendencies towards invisibility and inevitability requires critical imagination, and speculative methods help foster this for researchers and participants. This paper introduces speculative methods and explores their enactment in a research project that examined the social and ethical implications of datafication in higher education. Speculative methods are characterised by their non-representational, complexity-informed and inventive character and their temporal, epistemological and performative qualities. They have a complex relationship with time and temporality, attending to ‘not-yetness’; are epistemologically complex, producing problems and engaging with ambiguity; and act to create futures or realities they represent, in part through engaging publics at different scales and in different contexts. Methods inspired variously by speculative fiction and speculative design approaches have been used by digital education researchers to investigate and intervene in data futures and to challenge predictive, closed forms of data-driven future-making. The methodological value of speculation is explored here through discussion of a research project that involved ethnographic and speculative engagement with students at a research intensive university in Scotland. The research attempted to understand participants’ experiences of and perspectives on emerging data-driven technologies and practices, and what this meant for their relationship with the university. In this paper we analyse the design of and data generated through two particular speculative methods: data walking, and thinking otherwise. We focus on participants’ reflections on the methods used and show how speculation was central to efforts to prompt ethical reflection on data-driven practices. In the case of data walking, this involved sensitising participants to datafication processes, thereby making hidden practices visible to participants. A simple prompt to think otherwise, meanwhile, generated data regarding participants’ experiences and problems in the present while at the same time opening up possibilities of thinking otherwise about data futures. We close by relating these findings to wider considerations for speculative methods, focusing on the role of speculative objects as both instrument and output of research and exploring the significance of discursive closures in participatory research.